ChemInform Abstract: Lithium Chalcogenidotetrelates: LiChT—Synthesis and Characterization of New Li+ Ion Conducting Li/Sn/Se Compounds. Issue 41 (19th September 2013) - Kaib, Thomas; Bron, Philipp; Haddadpour, Sima; Mayrhofer, Leonhard; Pastewka, Lars; Jaervi, Tommi T.; Moseler, Michael; Roling, Bernhard; Dehnen, Stefanie
Abstract The new compounds (IV)—(VIII) are characterized by single crystal XRD and impedance spectroscopy.